NEGOSIASI IDENTITAS HOMOSEKSUAL DALAM KELOMPOK KEAGAMAAN KRISTEN - Syifa Salsabila, Astrid; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2020)
Christian gay individuals still has difficulties to fulfil their religious rights, one of them is affiliating themselves in a Christian-based group. It happens because heteronormativity is still dominant in Christian values, both in Protestant and Catholic teachings. Therefore, this study seeks to illustrate how homosexuals negotiate their sexual identities in Christian-based groups. Adopting critical phenomenology paradigm with interpretative method, this research does not only describe the negotiations, but also seeks to see whether there is a power relation to homosexuals in the sexuality discourse. Stella Ting-Toomeys’s Negotiation Identity Theory combined with Queer’s Theory was used to analyse the phenomenon. This research was not only conducted in-depth interviews with Christian homosexuals but also other members in the religious groups that are followed in order to overview the identity negotiations in the groups. Interviews with some religious leaders were also conducted in order to see how homosexuality is understood in Christianity views. The results of this study form the essence of homosexuals’ experience in negotiating their sexual identities in their Christian-based group that are followed. The formation of homosexual identity of the individuals is influenced by heteronormative teachings of Christianity so it created an identity struggle for the individuals. However, these individuals were still able to integrate their identities as homosexuals and Christians and eventually decided to become members of the Christian groups. Before negotiating identity in the religious groups, cognitive negotiations in homosexual individuals also have an ongoing role in determining the strategies that individuals will use to negotiate their identities. They use several strategies to negotiate their identities, from asserting, describing, modifying, and obscuring the identities so the identities can be accepted by themselves and other group members. Nevertheless, the process of negotiating the identity of individuals with each member of the religious groups will be different because it is also based on the closeness of the individual with each group member. The individuals did not fully neglected their homosexual identities despite some rejection in the groups. This study also still found power relations that rule how informants manage their homosexual identity based on heteronormativity values. However, these individuals try to change the power relations through the process of negotiating their homosexual identities in the groups.